Lifestyle Factors Influencing Mental Health Among University Students: A Literature Review - Budzeń, Dominika; Błaszczeć, Patrycja; Chmielnicki, Filip; Antos, Martyna; Burek, Rafał; Bochen, Jakub (Quality in Sport, 2026)
Background. Mental health among university students has become a significant public health concern, with an increasing prevalence of mental disorders observed in recent years. Lifestyle factors such as physical activity, sleep, diet, and stress are recognized as important determinants of mental well-being in this population. Aim. The aim of this review was to synthesize current evidence on the relationship between selected lifestyle factors and mental health among university students. Material and methods. A narrative review of the literature was conducted using PubMed and Scopus databases. Studies published between 2020 and 2026 were included. The search strategy involved keywords such as “mental health”, “students”, “diet”, “physical activity”, and “lifestyle”. Only English-language articles meeting predefined inclusion criteria were analyzed. A total of 25 studies were included in the final analysis. Results. The findings indicate that regular physical activity is associated with reduced symptoms of depression, anxiety, and stress, whereas low activity levels are linked to poorer mental health outcomes. Both insufficient and excessive sleep are associated with an increased risk of mental disorders. A healthy diet is associated with better psychological health, while poor dietary habits may exacerbate symptoms. Additionally, the COVID-19 pandemic negatively affected students’ mental well-being, whereas social support demonstrated a protective effect. Conclusions. Lifestyle factors play a significant role in shaping mental health among university students. Promoting healthy behaviors may improve well-being in this population; however, further longitudinal and intervention-based research is needed to better understand these relationships. These findings highlight the need for university-based prevention and mental well-being promotion programs.